2022
DOI: 10.3390/s22218193
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Acoustic Pick-Up for Straight Line-Type Sagnac Fiber Optic Acoustic Sensing System

Abstract: An improved acoustic pick-up is presented to enhance the acoustic sensing sensitivity of the straight line-type Sagnac fiber optic acoustic sensing system. A hollow elastomer cylinder is introduced into the system, and the optical fiber is tightly wound around the cylinder to construct the pick-up. The theoretical analysis was finished, and it showed that the improved pick-up will bring in an extra phase change and let the phase difference increase almost an order. The extra phase change will enhance the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To mitigate the cost of vibration-resistant and wear-resistant protection for long-distance fiber optics, a novel linear Sagnac fiber optic acoustic sensing system [13] was employed to minimize the communication fiber length and enhance the system's anti-interference capabilities.…”
Section: Study Of Recognition Systemmentioning
confidence: 99%
“…To mitigate the cost of vibration-resistant and wear-resistant protection for long-distance fiber optics, a novel linear Sagnac fiber optic acoustic sensing system [13] was employed to minimize the communication fiber length and enhance the system's anti-interference capabilities.…”
Section: Study Of Recognition Systemmentioning
confidence: 99%
“…Based on this system, an elastomer cylinder is proposed to improve the response sensitivity of the system. However, experimental results have shown that the introduction of the elastomer cylinder at different sound frequencies has a large difference in sensitivity [14] , so it is crucial to improve the elastomer cylinder.…”
Section: The Basic Composition Of the Systemmentioning
confidence: 99%
“…Various types of optical fibers exist today: bowtie, elliptical, pseudo-rectangle, elliptical core, panda [13,14] and others [15][16][17]. However, the process of developing improved types of designs does not stand still [18][19][20].…”
Section: Problem Contextmentioning
confidence: 99%